Hyperthermia-induced changes in liver physiology and metabolism: a rationale for hyperthermic machine perfusion - Thorne, Adam M.; Ubbink, Rinse; Brüggenwirth, Isabel M. A.; Nijsten, Maarten W.; Porte, Robert J.; de Meijer, Vincent E. (American journal of physiology: Gastrointestinal and liver physiology, 2020)
Liver transplantation is the standard treatment for end-stage liver disease. However, due to the ongoing disparity between supply and demand for optimal donor organs, there is increasing usage of extended criteria donor organs, including steatotic liver grafts. To mitigate the increased risks associated with extended criteria donor livers, ex situ oxygenated machine perfusion (MP) has received increasing attention in recent years as an emerging platform for dynamic preservation, reconditioning, and viability assessment to increase organ utilization. MP can be applied at different temperatures. During hypothermic MP (4–12°C), liver metabolism is reduced, while oxygenation restores the intracellular levels of adenosine triphosphate. The liver is quickly “recharged” to support metabolism when at normothermia (35–37°C) and to ameliorate the detrimental effects of ischemia/reperfusion injury during transplantation. During normothermia, MP can be applied to assess hepatocellular and cholangiocellular viability. MP at hyperthermic (>38°C) temperatures (HyMP), however, remains relatively understudied. The liver is an important component in the regulation of core body temperature and, as such, displays significant physiological and metabolic changes in response to different temperatures. Hyperthermia may promote vasodilation, increase aerobic metabolism and induce production of protective molecules such as heat shock proteins. Therefore, HyMP could provide an attractive reconditioning strategy for steatotic livers. In this review, we describe current literature on the physiological and metabolic effects of the liver at hyperthermia for human, rodents, and pigs and provide a rationale for using therapeutic HyMP during isolated liver machine perfusion to recondition extended criteria donor livers, including steatotic livers, before transplantation.